GAYA BELAJAR SISWA LAKI-LAKI DAN PEREMPUAN SMA NEGERI 3 TANJUNG MEDAN - Yusnabawi '; Rosmawati '; Elni Yakub Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrack This study entitled "Student Learning Styles Men And Women Sma Negeri 3 Tanjung Medan". This study aims to determine the student's learning style SMAN 3 Tanjung Medan, be it learning style visual, auditory Nor Kinesthetic. The formulation of the problem in this study is: How can the student's learning style illustration male, female student learning How description, and Are there differences in learning styles of boys and girls, if there is a difference it? from the formulation of the problem can be seen that the purpose of this study is: To determine the student's learning style Visual male and female students of SMAN 3 Tanjung Medan, To know the auditory learning styles of male students and female students of SMAN 3 Tanjung Medan, and to Kinesthetic learning styles of students know the male and female SMA 3 Tanjung Medan method used in this research is to use the comparative method, and the data processed in this study is data about student learning styles of men to women in SMAN 3 Tanjung Medan . And the population in this study were all students of SMAN 3 Tanjung Medan. Data collection tool was a questionnaire, which is about empathy questionnaire consisting of 30 questions. Keywords: Learning StylesStudentsMaleandFemaleStudents